Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1093/jac/dkn145
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of ESBL and Qnr determinants in Enterobacter cloacae in Algeria

Abstract: SHV-12, QnrS1, QnrB1 and QnrB4 were reported for the first time in Algeria. This study also described a co-expression of qnrS1 and qnrB4 by an SHV-12 producer isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 10 publications
8
35
1
Order By: Relevance
“…In the United States, Robicsek et al (34) showed that 20% and 11% of the Enterobacter isolates studied harbored the qnrA and qnrB genes, respectively (34) . In Algeria, Iabadene et al (15) reported the presence of qnrB1, qnrB4, and qnrS1 in clinical isolates of E. cloacae (15) . Dahmen et al from Tunisia reported that qnrB1 was the most prevalent gene among E. cloacae isolates, followed by qnrB2 and qnrS1, whereas qnrA was more prevalent among K. pneumoniae isolates (32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, Robicsek et al (34) showed that 20% and 11% of the Enterobacter isolates studied harbored the qnrA and qnrB genes, respectively (34) . In Algeria, Iabadene et al (15) reported the presence of qnrB1, qnrB4, and qnrS1 in clinical isolates of E. cloacae (15) . Dahmen et al from Tunisia reported that qnrB1 was the most prevalent gene among E. cloacae isolates, followed by qnrB2 and qnrS1, whereas qnrA was more prevalent among K. pneumoniae isolates (32) .…”
Section: Discussionmentioning
confidence: 99%
“…However, plasmid-mediated quinolone resistance (PMQR) has also been reported in several parts of the world (9) (10) (11) (12) (13) (14) . Plasmids carrying qnr genes widely vary in size and typically carry multiple resistance determinants (15) (16) . Qnr proteins are members of a pentapeptide repeat protein family, which is capable of protecting DNA gyrase and DNA topoisomerase IV from quinolone compounds (17) .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of ESBL bacteria in the ICU of Tlemcen Hospital may be related to the fact that cefotaxime is the first-line treatment; in fact, the heavy use of cefotaxime and ceftriaxone is considered a factor supporting the emergence of CTX-M enzymes [11]. CTX-M-15 with CTX-M-3 enzymes have been reported as prevalent ESBLs in the east [12] and centre [6,13,14] of Algeria, while only CTX-M-15 was found in our isolates. The fact is that CTX-M enzymes have recently and sharply accumulated in Enterobacteriaceae [1].…”
Section: Discussionmentioning
confidence: 99%
“…is increasingly identified as a cause of serious nosocomial infections. In recent years, ESBL production among these isolates is becoming a major clinical concern because of its ability to develop resistance to several classes of antimicrobial agents and has high potential for transmission of resistance to other bacterial species (16). In the current study, the most prevalent clinical Enterobacter species was E. cloacae (78.2 %) that showed the important role of this species in human infections, which was in agreement with other reports (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%